Urinary neurotransmitter analysis and canine behavior assessment - Schmidt, Teresa; Meller, Sebastian; Talbot, Steven Roger; Packer, Rowena Mary Anne; Volk, Holger Andreas (Frontiers in Veterinary Science, 2023)
Behavioural problems are highly prevalent in domestic dogs, negatively affecting the quality of life of dogs and their owners. In humans and dogs, neuropsychological or neurobehavioural disorders can be associated with deviations in various neurotransmitter systems. Evidence revealed correlations between urinary neurotransmitters and these disorders; however, a causal relationship has not yet been conclusively demonstrated. Non-invasive urinary neurotransmitter analysis may identify specific biomarkers, which enable a more differentiated assessment of canine behavioural disorders in the future and contribute to more effective neuromodulatory treatment decisions and monitoring. It could offer new insights into underlying pathomechanisms of canine neurobehavioural disorders. This study assessed urinary neurotransmitter levels and the descriptive behaviour profile of 100 dogs. No correlation was found between urinary neurotransmitters and the assessed behaviour profile; however, age-, sex- and neuter-related influences were identified. The lack of correlation could be explained by the many confounding factors influencing both behaviour and urinary neurotransmitter excretion, including age, sex and neuter status effects, and methodological issues e.g., low discriminatory power between anxiety and aggression in the descriptive behaviour evaluation. Urinary neurotransmitter testing could not be validated as a tool for canine behaviour evaluation in this study. However, reliable assessment methods with low susceptibility to human biases could be valuable in the future to support behavioural-phenotype diagnoses.